Tarifa pública: uma análise nos elementos de sua formação na atividade de transporte coletivo de passageiro na cidade de São Luís - MA - Silva Filho, Miguel Santiago (2010)
The problem of urban public transport fare is presented taking into account three perceptions of society. On one hand, the user population that believes the amount charged the fare is always greater than the cost calculated on spreadsheets for franchised businesses; on the other, the entrepreneurs of transportation that usually call for tariff adjustment, arguing that the tariff is below their operating costs and, finally, the regulator, which typically argues that the tariff meets a valuation in line with legislation and consistent with the cost of living in the city. Thus, this research aims at investigating the composition of the elements that make up the pricing structure of public transport in São Luis, capital of Maranhão and compare it with a new structure obtained from the balance sheets of companies. The study was characterized, according to the approach of the problem, as a quantitative research, with the instrument of data collection sheets, the cost of a sample of companies in the industry, as well as additional data from the local regulator. The rates are analyzed according to the traditional model of GEIPOT and its derivations. The results show that the rate is calculated according to the tariff calculation model practiced in the city, but there are distortions in the computed value with the value committed in the city. It was observed, based on the companies studied, there is misalignment as the price tariff calculated on the basis of cost accounting firms, showing that the cost structure of companies is different and that its structure determines the earning potential of each them in light of the current rate.